2012
DOI: 10.1186/2045-4015-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Medical specialty considerations by medical students early in their clinical experience

Abstract: Background Specialty selection by medical students determines the future composition of the physician workforce. Selection of career specialties begins in earnest during the clinical rotations with exposure to the clinical and intellectual environments of various specialties. Career specialty selection is followed by choosing a residency program. This is the period where insight into the decision process might help healthcare leaders ascertain whether, when, and how to intervene and attempt to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 26 publications
2
42
1
Order By: Relevance
“…In Gambia, all the medical students that participated in a study expressed interest in having career counselling during the period of their training [39], and from a similar study in Israel came the call for greater interest in the career selection of medical students [42]. The same study also earmarked the fifth year in medical school as the appropriate time for guidance to medical students on choice of specialty [42]. This was also highlighted in our study as more than half of the students (51.8 %) made their choice of specialty for specialization at that stage of their clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…In Gambia, all the medical students that participated in a study expressed interest in having career counselling during the period of their training [39], and from a similar study in Israel came the call for greater interest in the career selection of medical students [42]. The same study also earmarked the fifth year in medical school as the appropriate time for guidance to medical students on choice of specialty [42]. This was also highlighted in our study as more than half of the students (51.8 %) made their choice of specialty for specialization at that stage of their clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Another study that reported from India,[12] observed male medical students choosing internal medicine and surgery as their specialization, compared to females choosing OBG and pediatrics. Earlier study conducted by Subba et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the real process to determine the career of life begins during clinical rotations when students are exposed to both clinical and intellectual environments of various specialties. 1 In the Ministry of Health, the proportion of Saudi doctors who are working in health centers is (5.8%) which is lower than those in hospitals (16.9%). 2 According to the Ministry of Health, the numbers of medical schools in Saudi Arabia in the year of 2011 have been increased to 16 governmental medical schools, and five private ones.…”
Section: Introductionmentioning
confidence: 99%